2021
DOI: 10.1007/s11606-021-07053-4
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Governing Board Composition and Medicare Shared Savings Program Accountable Care Organizations Outcomes: an Observational Study

Abstract: BACKGROUND: Early studies of Medicare Shared Savings Program (MSSP) accountable care organizations (ACOs) suggested that physician leadership was an important driver of ACO success, but it is unknown whether the demographic and professional composition of current MSSP ACO governing boards is associated with ACOs' publicly reported outcomes. OBJECTIVE: To investigate whether governing boards with higher physician participation and greater female involvement have better outcomes. DESIGN: Cross-sectional observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In addition, our scoping review showed that the formation of HN was also influenced by the failure of pre-existing traditional structures to address complex inter-organizational coordination [e.g. mental and social care networks in Belgium and the UK ( Nicaise et al ., 2013 ; Larsen et al ., 2021 )], the unsatisfactory performance of traditional healthcare systems, the inefficiency of informal referral systems, the fragmentation of care, limited connectedness between health providers ( Nicaise et al ., 2013 ) and lack of mutualization of resources ( Palumbo et al ., 2017 ; Reimold et al ., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, our scoping review showed that the formation of HN was also influenced by the failure of pre-existing traditional structures to address complex inter-organizational coordination [e.g. mental and social care networks in Belgium and the UK ( Nicaise et al ., 2013 ; Larsen et al ., 2021 )], the unsatisfactory performance of traditional healthcare systems, the inefficiency of informal referral systems, the fragmentation of care, limited connectedness between health providers ( Nicaise et al ., 2013 ) and lack of mutualization of resources ( Palumbo et al ., 2017 ; Reimold et al ., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the role of legal policy frameworks was considered a critical contextual factor that laid the foundation for inter-organizational collaborations within HN in high-income ( Audet and Roy, 2016 ; Schneider et al ., 2019 ; Larsen et al ., 2021 ; Reimold et al ., 2022 ) and low-income (e.g. Zambia, South Africa, India) ( Schneider et al ., 2019 ) countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation